Pelaksanaan Manajemen Berbasis Sekolah (Studi Kasus pada SMA Negeri 2 Katingan Hilir) - Wilka Wilka; Bulkani Bulkani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
This study aims to: (1) To find out the implementation of school-based management (2) To find out the organization in the development of the curriculum used in the implementation of school-based management in Katingan Hilir 2 High School. This research was conducted in 2 (two) months, taking place at Katingan Hilir 2 High School, located on Tjilik Riwut km 2.5 road, Kasongan Lama Village. The method used in conducting this research is qualitative with the type of case study. The data collection techniques used are observation, interviews, and documentation. To test the objectivity and validity of the data used triangulation techniques, using reference materials, and holding member checks. Data analysis used is data reduction, data display, and conclusion. The results showed that at Katingan Hilir 2 High School in Katingan District the implementation of school-based management had gone well. Because this can be done well because of the collaboration between the principal and the board of teachers and the school community.